129 The prognostic; value of a 7-week high sensitivity Troponin T level after an acute coronary syndrome. (16th May 2012) - Ang, D S; Kao, M P; Lang, C C; Dow, E; Struthers, A D
Abstract : Background: High sensitivity Troponin T (HS-TnT) is a well established diagnostic and prognostic tool in acute coronary syndrome (ACS). However, its role in the convalescence phase after an ACS is unknown. Our first aim was to assess the prognostic utility of a single HS-TnT level at 7-week post ACS. Second, we evaluated whether any serial changes in HS-TnT between the index admission and 7 weeks post ACS had any link with prognosis. Third, we assessed whether the prognostic utility of HS-TnT is independent of various echocardiographic abnormalities. Methods: We measured HS-TnT levels in 326 consecutive patients at 7 weeks after an ACS event. The composite end point of death from any cause or acute myocardial infarction (AMI) was evaluated over a median duration of 30 months. Results: Patients in the third HS-TnT tercile were 6 times more likely to sustain a cardiovascular event compared to those in the first tercile [unadjusted RR 6.11 (95% CI 2.98 to 12.50)]. A high HS-TnT predicted adverse clinical outcomes independent of conventional risk factors, left ventricular dysfunction and left ventricular hypertrophy on echocardiography [adjusted RR 2.69 (95% CI 1.45 to 5.00)]. Patients with persistent HS-TnT elevation at 7 weeks were also at an increased risk of cardiovascular events compared to those with an initial high HS-TnT which then normalised [unadjusted RR 3.39 (95% CI 2.02 to 5.68)]. Conclusion: We have demonstrated for the first time the prognostic utility of a single 7-week HS-TnT measurement in routine ACS patients and that it could be used to assist medium term risk stratification in this patient cohort. Future studies should evaluate whether tailoring specific treatment interventions to higher risk individuals as identified by an elevated HS-TnT during the convalescence phase of ACS would improve clinical outcomes.